An investigation on internet shoppers' behavior - Fong, Angeline Chee Li (2001)
Shopping has become the fastest-growing use of the Internet. Consumers could buy products from any parts of the world at any time. Even consumers who have not used the Internet to purchase goods and services, claim to have use it for information searching that ultimately led to shopping in the traditional channels. Hence, Internet shopping is becoming a very popular activity among Internet users. Recently there have been several industry and academic studies investigating and profiling the Internet user. For example, it has been established that the Internet user is young and educated. What is still not very well known is who the Internet shopper is and what is the Internet shopper's behavior. While it is useful to profile the Internet user, from a marketing or advertising point of view it is more important to understand the Internet shopper. There is no evidence that suggests that the typical Internet user is also the typical Internet shopper. While market segmentation principles tell us that the shopper is going to be different for different products, it is still useful to understand and profile the typical Internet shoppers. This is especially important if the typical Internet shopper is going to be different from the typical Internet user. This research is a step in that direction. The main intention of this research is to find out what are Internet shoppers behavior. It would also discuss whether Internet user tend to be Internet shoppers. Other main factors inclusive of security perception, better bargain and better brand comparison perceptions were tested to find out whether it would influence Internet shopping frequency. Regression and descriptive analyses were deployed. Implications of the study and suggestion for future research were discussed in the final section.